Comparison of Three Different IBD Vaccination Protocols in Broiler Chicken—Efficacy, Serological Baselines and Histo-Pathological Lesions in the Bursa of Fabricius - Marcin Śmiałek; Joanna Kowalczyk; Michał Gesek (Animals)
Background: Infectious bursal disease (IBD) is a highly infectious disease of chicken found in all latitudes, due to the very high resistance to environmental conditions and commonly used disinfectants of the IBD virus (IBDV). Methods: This study was conducted to evaluate three IBD vaccination protocols in broiler chicken in terms of their effectiveness (clinical observations and production performance of the flock), estimation of serological baseline values (with the use of two different commercial ELISA kits) and the degree of progression of BF lesions (histopathological lesion score (HLS)) after vaccination. The three protocols were (I) single vaccination using an intermediate plus vaccine, (II) double vaccination with an intermediate vaccine and (III) double vaccination with an intermediate plus vaccine. Results: Birds on farms vaccinated with protocol II were characterized by the lowest antibody titers in both ELISA tests and the lowest average HLS. The highest IDEXX titers were obtained in birds vaccinated with protocol III, while in the BIOCHEK test the highest titers were obtained for birds vaccinated with protocol I. Protocols I and III were characterized by similar HLSs. Birds vaccinated with protocols I and III had higher immune uniformity. Conclusions: The estimated serological baseline values and the degree of HLSs presents a clear picture of the differences between the different vaccination protocols and allows their adaptation for different farms depending on the current IBD epidemiological situation.